2014
DOI: 10.1093/mnras/stu1230
|View full text |Cite
|
Sign up to set email alerts
|

A UV flux constraint on the formation of direct collapse black holes

Abstract: The ability of metal free gas to cool by molecular hydrogen in primordial halos is strongly associated with the strength of ultraviolet (UV) flux produced by the stellar populations in the first galaxies. Depending on the stellar spectrum, these UV photons can either dissociate H 2 molecules directly or indirectly by photo-detachment of H − as the latter provides the main pathway for H 2 formation in the early universe. In this study, we aim to determine the critical strength of the UV flux above which the for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 75 publications
6
82
0
Order By: Relevance
“…However, any theoretical model that attempts to explore the abundance of such sites is extremely sensitive to the choice of Jcrit. For example, an order of magnitude increase in Jcrit can reduce the DCBH number density at z = 6 by three orders of magnitude (Dijkstra et al 2008;Latif et al 2014;Dijkstra et al 2014). This emphasizes the need to understand and calculate the value of Jcrit produced by galaxies composed of Pop II stars in the early Universe.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, any theoretical model that attempts to explore the abundance of such sites is extremely sensitive to the choice of Jcrit. For example, an order of magnitude increase in Jcrit can reduce the DCBH number density at z = 6 by three orders of magnitude (Dijkstra et al 2008;Latif et al 2014;Dijkstra et al 2014). This emphasizes the need to understand and calculate the value of Jcrit produced by galaxies composed of Pop II stars in the early Universe.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Latif et al (2014) and SG15a have shown that omitting this process introduces a factor of two our chemical model, using the rate given in Martin et al (1996).…”
Section: Appendix A: Chemical Networkmentioning
confidence: 99%
“…Such a black hole mass is in the range of masses associated to direct collapse of warm gas inside atomic cooling haloes at high redshift (e.g. Oh & Haiman 2002;Lodato & Natarajan 2006;Begelman et al 2006Begelman et al , 2008Agarwal et al 2012;Latif et al 2013Latif et al , 2014Choi et al 2015). We did not allow more BH formation after the formation of the first one.…”
Section: Sink Particles and Black Hole Accretionmentioning
confidence: 99%
“…If there is no molecular hydrogen to avoid fragmentation (e.g. Agarwal et al 2012;Latif et al 2013Latif et al , 2014 and there is an efficient outward AM transport (Choi et al 2015) such a scenario could favor the formation of a BH seed of ∼ 10 4 −10 6 [M ], e.g. Begelman et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…In three-dimensional (3D) simulations, the self-shielding depends on the direction as well, due to a spatial variation of the gas density and its temperature. This direction dependence can cause a substantial difference in the estimate of J crit , between 3D and 1D simulations (e.g., Shang et al 2010;Latif et al 2014a). Moreover, existence of the X-rays could increase the hydrogen ionization fraction and the free electron fraction, which promotes the H − and H 2 formation via the electron-catalysed reactions.…”
Section: Introductionmentioning
confidence: 99%